DESENVOLVIMENTO E APLICAÇÃO DE METODOLOGIA ANALÍTICA PARA A DETERMINAÇÃO DIRETA DE Pb, Cd E Cr EM AMOSTRAS DE MEL UTILIZANDO ESPECTROMETRIA DE ABSORÇÃO ATÔ MICA COM ATOMIZAÇÃO ELETROTÉRMICA EM FORNO DE GRAFITE - Andrade, Camila Kulek de (2013)
In the honey production, Apis melífera honeybees roam vast areas and it come into contact with various environmental compartments. In this process, they can accumulate contaminants, especially metal species, and honey can act as an indicator of environmental quality, reflecting the concentrations found in the environment. The quantification of metals in honey is still considered an analytical challenge due to the complexity of the matrix. Many analytical methods developed involve a step of pretreatment of the sample prior to quantification of the metals that may cause sample contamination or loss of analyte. In this study were established analytical basis for the direct determination of metal species in the honey samples using atomic absorption spectrometry. An analytical protocol was developed and implemented for the determination of Pb, Cd and Cr in honey samples directly, i.e., without pretreatment step, using the Atomic Absorption Spectrometry with Electrothermal Atomization in Graphite Furnace. For this purpose, aqueous suspensions of honey were prepared and inserted directly into the graphite furnace. Addition of nitric acid and hydrogen peroxide in aqueous suspensions of honey possible the elimination of the organic matrix of the sample during the pyrolysis step of heating program of GF AAS. The programs of the heating graphite furnace were optimized for each element. The need to use chemical modifiers such as palladium, ammonium dihydrogenphosphate and magnesium nitrate was evaluated. In the determination of cadmium was necessary to employ the universal modifier (Pd-Mg) in order to avoid losses of the element through the steps of heating the graphite furnace. The analytical characteristics of the methods were evaluated through calibration tests, evaluation of sensitivity, precision and accuracy. Aqueous analytical curves were used for determinations of Pb and Cr, and in middle of fructose in the quantification of Cd in honey samples. The quantification limits were low with values of 2.0, 5.4 and 9.4 ng g?¹ for Cd, Pb and Cr, respectively. Estimates of relative standard deviation was below 10% in tests of repeatability and intermediate precision. The recoveries obtained in the accuracy tests were adequate and ranged between 90% and 105% for the three elements. So, after validation of the developed methods was performed applying the analytical methodology in 52 honey samples from different regions of the State of Paraná. The levels of Pb, Cd and Cr ranged from > 2.0 ng g?¹ to 413 ng g?¹ and are consistent with the literature. In general, it is noted that the concentration of elements followed the order: Pb > Cr > Cd, Pb with concentrations in the range of 86-413 ng g?¹, and for Cr 46-132 ng g?¹ and 2.0-16.3 ng g?¹ to Cd, respectively. A chemometric tool was applied to evaluate data generated for honey samples of Paraná. Through Principal Component Analysis (PCA) was observed that the honey samples obtained in the Center-South and Southeast regions have similar contents of Pb and Cd, and the higher content of Pb was obtained in the sample from Candói (3) and Cd in the sample from Rio Piquiri (4). This may be related to the fact that these places have their economy based on agriculture. The presence of these metals in pesticides and fertilizers and also in the atmosphere, because the particulate matter from the smoke emission vehicle, causes his levels are higher in these regions. The samples of the regions West, Southwest, Northwest and Metropolitan had similar contents of Cr. Therefore, with the PCA, it was possible to note that the honey samples from Paraná are qualified according to their geographical region and levels of trace elements. Based on calculations of daily ingestion of honey, it was observed that the honeys from Paraná also present food safety in relation to the content of Pb, Cd and Cr in foods ingested by consumption of this product.